2021
DOI: 10.1016/j.pmedr.2021.101496
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic physical activity to improve memory and executive function in sedentary adults without cognitive impairment: A systematic review and meta-analysis

Abstract: Highlights Aerobic physical activity interventions had a large effect on memory. Aerobic physical activity interventions had a small effect on executive function. Meeting U.S. physical activity guidelines resulted in a large effect on memory. Studies with a no treatment control had a large effect on memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
2
29
0
2
Order By: Relevance
“…La combinación de ejercicio aeróbico y resistencia muscular, mejora significativamente la función física y la fragilidad en adultos mayores con obesidad. Por lo dicha intervención en el estilo de vida puede considerarse una estrategia efectiva para mitigar las complicaciones metabólicas y físicas relacionadas con el envejecimiento y la obesidad, con el objetivo final de prolongar la independencia funcional y la calidad de vida de los adultos mayores con obesidad (40) .…”
Section: Discussionunclassified
“…La combinación de ejercicio aeróbico y resistencia muscular, mejora significativamente la función física y la fragilidad en adultos mayores con obesidad. Por lo dicha intervención en el estilo de vida puede considerarse una estrategia efectiva para mitigar las complicaciones metabólicas y físicas relacionadas con el envejecimiento y la obesidad, con el objetivo final de prolongar la independencia funcional y la calidad de vida de los adultos mayores con obesidad (40) .…”
Section: Discussionunclassified
“…These positive, brain ageing reducing effects on PCC were achieved with over a decade of PA. PCC functional connectivity is also reduced in the early stages of AD [ 151 ]. Meta-analysis of randomised, controlled trials, in healthy adults aged 50 and older, reported improved memory, executive function, auditory attention, cognitive speed, visual attention motor function and cardiorespiratory fitness after aerobic PA programmes [ 152 , 153 ]. Guidelines for healthy ageing recommend a personalised, PA regime that enables at least 150 min of moderate-intensity aerobic activity, or 75 min of vigorous-intensity aerobic activity combined with at least two days of muscle-strengthening activities per week [ 154 ].…”
Section: Physical Activity Delays Ageing-related Changesmentioning
confidence: 99%
“…With progressive sedentariness, it is easier to gain weight. In contrast, the foundational feature of a healthy lifestyle is regular physical activity (Mok et al, 2019), which has been shown to not only improve mood and decrease anxiety (Rodriguez-Ayllon et al, 2019), but also improve memory and executive functioning (Hoffmann et al, 2021)-making it easier to self-regulate and socialize.…”
Section: Lifestyle As a Networkmentioning
confidence: 99%